Contamination of dab (Limanda limanda) with explosive chemicals leaking from marine dumped munition - Kammann, Ulrike; Töpker, Verena; Schmidt, Nicole; Rödiger, Marcellus; Aust, Marc-Oliver; Gabel, Michael; Scharsack, Jörn Peter (PANGAEA, 2024)
Conventional munition dumped into the North Sea and the Baltic Sea close to the German coastline is corroding. A major concern is that biota, including fish, take up toxic explosives leaking into marine environments. With the present study, we investigated bile fluids of fish living in close proximity to munition dumping sites for the explosives 2,4,6-trinitrotoluene (TNT), its metabolites 2-amino-4,6-dinitrolouene and 4-amino-2,6-dinitrolouene as well as octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) using HPLC-MS/MS (high performance liquid chromatography with mass selective detection) as device. The flat fish species common dab (Limanda limanda) was used as a model, since it lives in the vicinity of dumping sites and exhibits minor migratory activity.
Keywords: Baltic Sea; bile; HMX; metabolites; North Sea; TNT